Process Characterization of 32nm Semi Analytical Bilayer Graphene-based MOSFET - Noor Faizah Z.A.; Ahmad I.; Ker P.J.; Menon P.S. (EDP Sciences, 2023)
Ballistics; Display devices; Gate dielectrics; Graphene; Graphene devices; Graphene transistors; Hafnium oxides; High-k dielectric; Manufacture; Ohmic contacts; Reconfigurable hardware; Analytical expressions; Ballistic transports; Channel potential; Drain-induced barrier lowering; HIGH-K metal gates; Ideal ohmic contacts; Process characterization; Sub-threshold swing(ss); MOSFET devices